PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KABUPATEN SIJUNJUNG - Jufrizal Kurniawan; F. Yasmeardi; Dian Rizke (Jurnal Public Administration, Business and Rural Develoment Planning, 2020)
The purpose of the research carried out is 1. To find out the level of work motivation of Sijunjung District Civil Service Police employees, 2. To find out the level of Job Satisfaction of Civil Service Police Unit Sijunjung District, 3. To find out the Effect of Work Motivation on Employee Satisfaction of Civil Service Police Unit employees Sjaja Regency Praja. For this reason the research method is a quantitative approach. The results of the study provide the following conclusions: 1. Work Motivation Variables in this study were measured by the number of 20 question items by producing an average accumulation of a score of 3.45 with the achievement of the TCR percentage reaching 69.70%. So the Work Motivation of Satpol PP employees is relatively good. 2. Job Satisfaction Variables in this study were measured using 28 statement items to produce an average accumulated score of 3.37 with the achievement of the TCR percentage reaching 67.44%. So job satisfaction with Satpol-PP employees is relatively good. 3. Based on the regression test Y = a + bX obtained Y = 10,587 + 0.773 (Work Motivation), this shows the positive influence generated by Work Motivation on Job Satisfaction. This means that if Work Motivation (X) is increased by 1 point, it will have an effect on Job Satisfaction of 10,587 + 0.773. From the results of the determinant coefficient test through SPSS 21.00, the value of the determinant coefficient (R-Square) of Work Motivation (X) is equal to 0.662 or 66.2%. Thus variations in the increase and decrease in Job Satisfaction (Y) can be explained by the variable Work Motivation by 66.2%, while the remaining 33.8% Job Satisfaction is influenced by other factors not included in the studied variables. Based on the hypothesis test (t test) obtained the value of t count is 11,616 while the t table is equal to 2,045. Thus t arithmetic> t table, so that (Ho) is rejected and (Ha) is accepted, meaning that there is an influence between Work Motivation and Job Satisfaction. From the conclusions above, it is suggested the following: 1. To achieve goals in an agency the need for leadership to improve and require employee morale by providing appropriate and good motivation, 2. To achieve Job Satisfaction the need for leaders to recognize the ability of each employee so that leaders should provide training to employees in adding insight and skills in accordance with the placement of these employees, 3. Employee Work Motivation is very influential in achieving good Job Satisfaction for that leadership must motivate employees so that employee morale increases.